Ugocsa vármegye levéltárának történetéből - Csatáry György; Чотарі Юрій; Yurii Chotari (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-„RIK-U” Kft., 2017)
Annak ellenére, hogy Ugocsa Magyarország egyik legkisebb vármegyéje volt, levéltára mégis gazdag múltat mondhat magáénak. Az I. világháború végéig az évszázados iratörökség a többi szomszédos vármegye gyűjteményeihez hasonlóan azonos rendeletek és törvények alapján rendeződött. A megyei levéltárakban őrzött iratok sorsát, rendszerezésének módszereit, valamint a fizikai megőrzésének feltételeit jelentősen befolyásolták a XX. századi rendszerváltások. Igaz ugyan, hogy mindegyik államalakulat fontos kérdésnek deklarálta a „régi iratok” megőrzését az utókor számára, de az igényekhez képest keveset tett annak megvalósításáért. Szerencsére mindig akadtak önzetlen emberek, akik rendszerint csekély bérért felvállalták az iratrendezés nehéz feladatát. Ezúttal az ugocsai levéltári helyzet alakulását tekintjük át.

Резюме. Попри те, що Угочанський комітат був однією з найменших адміністративних одиниць на території історичної Угорщини, Угочанська архівна колекція є однією з найбагатших. До кінця Першої світової війни багатолітні колекції документів систематизовувалися на основі єдиного законодавства та розпоряджень. На долю збережених в архівах документів сильно впливали часті державні зміни на території комітату. Кожне нове державне утворення наголошувало на важливості збереження «старовинних паперів», але дуже повільно втілювало рішення такого роду в життя. Переглядаючи оригінальні джерела, було приємно переконатися в тому, що завжди існували безкорисливі люди, які за мізерну зарплату поступово упорядковували архіви. На цей раз ми ознайомимо читачів зі станом архівної справи в Угочанському комітаті.

Abstract. Despite the fact that Ugocsa was one of Hungary’s smallest counties, its archive has a rich past. Till the end of World War I, the classification of the century-old document heritage was done on the basis of orders and laws similar to the collections of the neighbouring counties. The fate of the documents kept in county archives, the methods of their systematization, as well as the conditions of their physical maintenance were significantly influenced by changes of regimes of the 20th century. Although every regime declared the question of sustaining the ‘old documents’ for the posterity as important, they did little in comparison with the demands in order to realize this sustaining. Fortunately, there were always unselfish people who undertook the difficult task of document arrangement, usually for extremely low salary. The present article provides insights into the formation and development of the Archive of Ugocsa County.
З історії Угочанського комітатського архіву
From the History of the Archive of Ugocsa County
https://kmf.uz.ua/wp-content/uploads/2017/12/Acta2017_szines.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00005708
Keywords: Ugocsa vármegye; levéltár; iratok